The holistical foundation ofthe phisical-metaphysic structure ofthe beauty in Heraclitus and hers levéis of realization (Iter, 2022)
We maintain in accord with Heraclitus that beauty is a complex phenomenonand holds many levels of realization. Thus. we recognize a strictly human level. whereaesthetic experience properly is realized. although there are some conditions wichallow establish diferences in this level of experience. Nevertheless. we also agree withHe rae i tus. in regard to consider parí of the human aesthetic experience permiting theacknowledgment of a kind o f transcendent aesthetic connecting our perception andexperience to a phisical level of reality. even more, with one metaphisical.
Keywords: Heraclitus. beauty, holism